URGENSI MEDIA DIGITAL DALAM BERDAKWAH PADA MASA PANDEMI COVID-19 - Mistarija Mistarija (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Digital media has progressed rapidly and has become a big industry in today's world society. Digital media has given people the opportunity to meet and interact in cyberspace, so that information about various events that occur in all corners of the world can be spread quickly, penetrating the boundaries of territory and time. Therefore, the media should be used by Muslims so that da'wah activities continue to run in the midst of the community during the Covid-19 pandemic that is hitting the world. The media should serve as a bridge between the da'i and mad'u to create and encourage the active involvement of Muslims in an effort to help motivate them to continue living their lives according to Islamic values. Because, in a pandemic, people are required to implement a new lifestyle in the form of social distancing and physical distancing. Thus, da'wah in the form of tabligh through the pulpit where the da'i and mad'u meet directly in one place such as mosques and mushalla can no longer be carried out freely as usual. This requires the da'i to continue to be creative and innovate in formulating the implementation of da'wah during the pandemic so that it continues to run well. One solution is to utilize digital media with all its applications.Keyword : Da’wah, Digital Media, Covid-19 Pandemic